2017
DOI: 10.20489/intjecse.330045
|View full text |Cite
|
Sign up to set email alerts
|

Father Involvement, Early Intervention Program and Well-being of Children with Special Needs

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…While mothers/mums are seen as the primary EI target and often exclusive participants in both EI service delivery and EI research, fathers/dads are noticeably absent from EI services and there has been very little research conducted to understand this phenomenon. This knowledge gap is strongly reflected in recent studies on parental involvement in EI, indicating that mothers/mums are the predominant research focus (Bagner, 2013;Bagner & Eyberg, 2003;Curran, 2003;Zin & Nor, 2017), yielding inconclusive findings about fathers/dads' need of support in EI and the impact of their participation in EI programmes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While mothers/mums are seen as the primary EI target and often exclusive participants in both EI service delivery and EI research, fathers/dads are noticeably absent from EI services and there has been very little research conducted to understand this phenomenon. This knowledge gap is strongly reflected in recent studies on parental involvement in EI, indicating that mothers/mums are the predominant research focus (Bagner, 2013;Bagner & Eyberg, 2003;Curran, 2003;Zin & Nor, 2017), yielding inconclusive findings about fathers/dads' need of support in EI and the impact of their participation in EI programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Although research literature to date on fathers/dads role and involvement has mainly focused on fathering within the context of families of typically developing children, with the majority of evidence indicating that the involvement of fathers/dads during early years can have a positive impact on child outcomes in a variety of developmental domains and across different developmental stages (Paquette & Dumont, 2013), it is believed that a similar shift in role responsibilities of fathers/dads and their involvement is expected in families of children with SEN/D. For example, the positive participation of fathers/dads contributes to the enduring relationships in families of children with SEN/D, lead to optimal child and family developmental outcomes (Zin & Nor, 2017). In the context of EI, research has also found that directly involving fathers/dads in EI programmes not only promotes the effectiveness of intervention programmes within the context of a family and a child with SEN/D (Ingber & Most, 2012;Justin Dyer et al, 2009;Zaidman-Zait et al, 2018), but also enhances fathers/dads' understanding of their role identity as individuals, lead to higher levels of engagement in EI-related activities, vocal communication, and parental sensitivity (Fox et al, 2015;Roopnarine & Yildirim, 2019).…”
Section: Introductionmentioning
confidence: 99%